Everything you need to know about dealing with stalking - Wright, Cynthia (Cynthia S.) (New York : Rosen Pub. Group, 2000)
Discusses the nature and possible causes of stalking and provides advice on how to handle being stalked.
Includes bibliographical references and index.
Keywords: Stalking -- United States -- Juvenile literature; Teenage girls -- Crimes against -- United States -- Prevention -- Juvenile literature; Stalking